Spatial distribution of populations agave weevil Scyphophorus acupunctatus (Coleoptera: Dryophthoridae) in the State of Mexico, Mexico - González Dávila , Melisa; Ramírez Dávila, José Francisco; Acosta Guadarrama , Agustín David; Figueroa Figueroa , Dulce Karen (Revista Colombiana de Entomología, 2024)
Agave is one of the most representative plant groups in Mexico. Its importance lies in its ecological, cultural, and economic value. However, it faces several limitations, especially pest infestations, one of the most important of which is the agave weevil Scyphohphorus acupunctatus Gyllenhal (Coleoptera: Dryophthoridae), which has acquired importance because it bores the stalks into the interior of the plant, causing lesions that are subsequently infected by fungi and/or bacteria until the plant dies. The objective of this study was to determine the spatial distribution of agave weevil populations in two localities in the municipality of Malinalco using spatial analysis of the distance index, SADIE. The results showed that the Ia and Ja indices of the agave weevil populations present values greater than 1, which indicates an aggregated type spatial distribution in the two plots where the study was carried out. Short-term spatial and temporal stability was also determined with the Im index. Density maps were generated for each sampling in the two plots, with the maps that were elaborated, the infested surface in each plot was calculated, the results show us the distribution of the pest, and the alternatives for sustainable management of this pest are proposed.